2018
DOI: 10.1002/chem.201801272
|View full text |Cite
|
Sign up to set email alerts
|

DNA Oxidation Photoinduced by Norharmane Rhenium(I) Polypyridyl Complexes: Effect of the Bidentate N,N′‐Ligands on the Damage Profile

Abstract: Re -polypyridyl complexes have interesting and distinctive photochemical and photosensitizing properties. This work describes the capability to induce (or photoinduce) DNA damage of three Re -complexes with a naturally occurring alkaloid called norharmane (nHo) as ligand: [Re(CO) (nHo)(L)]CF SO where L=2,2'-bipyridine (ReBpy), phenanthroline (RePhen) or dipyrido[3,2-a:2',3'-c]phenazine (ReDppz). The interaction of the complexes with DNA was investigated by steady-state and time-resolved spectroscopy. Data show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 81 publications
1
21
0
Order By: Relevance
“…[45][46] Recently, it was demonstrated that silver(I) complexes of nHo were light stable and also cytotoxic against different cell lines 47 . Moreover, the complexes used in this work were cytotoxic against A549 cells, 37 phototoxic against S. typhimurium and showed photosensitizing potential against plasmid DNA 48 .…”
Section: Accepted Manuscriptmentioning
confidence: 89%
“…[45][46] Recently, it was demonstrated that silver(I) complexes of nHo were light stable and also cytotoxic against different cell lines 47 . Moreover, the complexes used in this work were cytotoxic against A549 cells, 37 phototoxic against S. typhimurium and showed photosensitizing potential against plasmid DNA 48 .…”
Section: Accepted Manuscriptmentioning
confidence: 89%
“…Similar dose-dependencies have already been reported for other related βCs. [37][38][39][40]44,45,57 Briefly, the number of DNA modifications increases linearly with the compounds' concentration. For all the investigated alkaloids Fpg-sensitive sites were found to be produced with the highest efficiency, whereas SSBs were produced with a very low or even null efficiency (<0.07 modifications/10 4 bp).…”
Section: Dna Damage Photoinduced By N-methyl-βcsmentioning
confidence: 99%
“…Moreover, the rich photophysical properties of the Re(CO) 3 core have given rise to promising new photodynamic therapy (PDT) and photoactivated chemotherapy (PACT) agents, owing to their ability to generate singlet oxygen ( 1 O 2 ) and carbon monoxide (CO) upon irradiation. [19][20][21][22][23][24] These same photophysical properties of Re(CO) 3 complexes have also been leveraged for diagnostic applications. When diimine ligands with low-lying empty π* orbitals, such as bipyridine and phenanthroline, are employed as equatorial ligands, the resulting Re(CO) 3 compounds are often photoluminescent, owing to the resulting long-lived triplet metal-toligand charge transfer ( 3 MLCT) emissive states that are accessible to these complexes.…”
Section: Introductionmentioning
confidence: 99%
“…TRIP kills cancer cells via the induction of endoplasmic reticulum (ER) stress, marking a notable divergence from the well‐established DNA‐binding mechanism of Pt(II) chemotherapeutics. Moreover, the rich photophysical properties of the Re(CO) 3 core have given rise to promising new photodynamic therapy (PDT) and photoactivated chemotherapy (PACT) agents, owing to their ability to generate singlet oxygen ( 1 O 2 ) and carbon monoxide (CO) upon irradiation [19–24] …”
Section: Introductionmentioning
confidence: 99%